The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jpainsymman.2012.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Palliative Care on the Heart Failure Care Team: An Innovative Research Methodology

Abstract: Context-There is a growing call to integrate palliative care for patients with advanced heart failure (HF). However, the knowledge to inform integration efforts comes largely from interview and survey research with individual patients and providers. This work has been critically important in raising awareness of the need for integration, but it is insufficient to inform solutions that must be enacted not by isolated individuals but by complex care teams. Research methods are urgently required to support system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 75 publications
(67 reference statements)
0
26
0
Order By: Relevance
“…We used an innovative methodological team sampling unit (TSU) approach that explores how health‐care teams are defined and experienced by individuals with HF . Five Canadian cities in three provinces with differing health‐care organization for primary and secondary care and for the care of heart failure patients were identified as recruitment sites (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…We used an innovative methodological team sampling unit (TSU) approach that explores how health‐care teams are defined and experienced by individuals with HF . Five Canadian cities in three provinces with differing health‐care organization for primary and secondary care and for the care of heart failure patients were identified as recruitment sites (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…, Lingard et al . ). Initially, study investigators used constructivist grounded theory (Charmaz ) with the goal of informing theoretical frameworks for educational training and policy development involving palliative care for patients with advanced HF (Carstairs , Chattoo and Atkin ).…”
Section: Methodsmentioning
confidence: 97%
“…This project occurred within a multi-site qualitative study of health care within complex, distributed Canadian HF care teams (LaDonna et al 2017, Lingard et al 2013. Initially, study investigators used constructivist grounded theory (Charmaz 2014) with the goal of informing theoretical frameworks for educational training and policy development involving palliative care for patients with advanced HF (Carstairs 2010, Chattoo andAtkin 2009).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Lingard et al (2013) reported that HF patients had fewer choices regarding end-of-life care compared to cancer patients. In this study 93% of respondents agreed or strongly agreed that a dying person should be allowed to make decisions about their physical care indicating that cardiac nurses have a clear understanding of the importance of keeping the patient at the centre of their care.…”
Section: Attitudes To Caring For Dying Patients and Their Familiesmentioning
confidence: 99%